Síntese e caracterização de complexos organometálicos de Rutênio(II) como potenciais catalisadores para formação de ligações N-C - Caetano, Bárbara Pires de Sene (2023)
In this work, three N-heterocyclic carbene ligands were synthesized and characterized from the ring-closing reaction of its corresponding diimine donors using tetrafluoroboric acid. These ligands were used to synthesize organometallic complexes of general formula [RuCl2(NHC)(p-cym)] using the metallic binuclear [RuCl(µ-Cl)2(p-cym)]2 (p-cym = para-cymene) as precursor. All compounds characterizations were performed using ultraviolet and visible spectroscopy, infrared spectroscopy, hydrogen and carbon nuclear magnetic resonance, elemental analysis and molar conductivity. Ultraviolet and visible and infrared spectra showed results according to literature for both ligands and complexes. Hydrogen nuclear magnetic resonance was fundamental to identify the structures of the ligands and its corresponding complexes. It was possible to prove the coordination of the ligand to the metallic center due to the presence of double doublets characteristic of the sp² hydrogens of the p-cym ligand in the region between 5.5 and 4.5 ppm. The complexes were Applied as pre-catalysts in reactions of N-alkylation of amines via hydrogen borrowing with alcohol and showed good catalytic activity. [RuCl2(IMes)(p-cym)] complex performed better in the absence of base, with a TON value of 152.0 and TOF of 6.3 h-1, and [RuCl2(iPr)(p-cym)] complex had its best performance in presence of base, with a TON value of 226.7 and TOF of 9.4 h-1. Keywords: N-heterocyclic carbenes, Organocatalysis, Ruthenium complexes, Organometallic complexes, Homogeneous catalysis.